ANALYSIS OF FINANCIAL PERFORMANCE OF PETROCHEMICAL INDUSTRY IN INDONESIA DURING PRE AND POST COVID-19 (STUDY CASE: PT CHANDRA ASRI PETROCHEMICAL TBK) - Wicaksono, Alloysius
During the COVID-19 pandemic, every company in every industry saw a drop in financial performance. This was also the case for companies in the petrochemical industry, which saw a decline in financial performance. As a result, the stakeholders who are expected to make decisions based on the situation must comprehend the situation. The evaluation of a company's financial performance serves as a guideline for determining how long the company can survive. Either for the present or in the future. As a result, the researcher made the decision to examine the company's financial performance, which includes the Profitability Ratio, Liquidity Ratio, Activity Ratio, and Solvability Ratio. PT Chandra Asri Petrochemical Tbk is the subject of this investigation. Researchers want to know how the company's financial performance was before and after COVID-19.